Sanford Underground Research Facility’s approach to school education, community activities, and public outreach - Horn, Markus; Woodward, Erin Lorraine (Frontiers in Physics, 2023)
An emphasis on outreach and education is embedded in SURF's mission statement: "to advance world-class science and inspire learning across generations." To achieve this mission, SURF goes beyond established science communication methods, including operating an open-to-the-public visitor center, hosting multiple public outreach events per month, and an annual city-wide science festival. Furthermore, SURF is training K-12 science educators, developing school curriculum units, and providing classroom materials, based on science researched at the laboratory. The strategic approach, specific methods, and successful outcomes of these programs, which are based on SURF's science, location, and community, may serve as examples for effective science education, public outreach, and community engagement.